Squamous cell carcinoma arising from neglected meningocele - Wani, Abrar A. (Surg Neurol Int, 2016)
BACKGROUND: A neural tube defect (NTD) is a common congenital anomaly with an incidence of 6.57–8.21 per 1000 live births. Patients usually present early because of obvious swelling or due to neurological deficit. However, neglecting the obvious cystic swelling on the back till its transformation into malignant tumor is rare. CASE DESCRIPTION: We describe a case of malignant transformation of meningocele in a 60-year-old man. Magnetic resonance imaging showed sacral meningocele. Neurological examination revealed intact motor and sensory examination with normal bladder and bowel function. There were no signs of meningitis and hydrocephalus. Excision was done and biopsy revealed it as squamous cell carcinoma. CONCLUSION: Meningocele should be treated early and possibility of malignant change should be kept in mind in neglected cases presenting in adulthood.